Modeled sustainability impacts of increasing pork consumption among adults in the United States - Conrad, Zach; Repoulis, Vincent; Zavela, Catherine (Frontiers in Nutrition, 2025)
IntroductionLittle is known about the role of pork in sustainable diet patterns, given that it is often aggregated with other animal proteins or not evaluated at all. To address this gap, this study modeled the sustainability impacts of replacing different protein foods with pork in a nationally representative sample of adults in the United States (US).MethodsData on dietary intake, greenhouse gas emissions (GHGE), cumulative energy demand, water scarcity footprint, land, pesticides, fertilizer nutrients, food prices, and diet quality were obtained from publicly available repositories. A food substitution model was constructed to evaluate the change in each sustainability impact when 1–3 servings of beef, poultry, seafood, eggs, or legumes were replaced by pork.ResultsModeled substitution of beef with pork was associated with reductions in GHGE, land, pesticides, and fertilizer nutrients by 11–35%, and substitution of seafood with pork was associated with reductions in cumulative energy demand by 6% and diet cost by <1%. All other substitutions led to an increase in sustainability impacts of up to 5%, including all outcomes associated with substituting poultry, eggs, and legumes with pork.DiscussionThe US federal government can play an important role in improving data collection methods that distinguish between pork and other meats. This can facilitate further research to evaluate sustainability trade-offs, which can inform clinical practice and public policy to support informed food choices for consumers.